1993
DOI: 10.1007/bf01956746
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and diagnostic approach in type I tyrosinaemia in an infant with cytomegaly virus infection and bacterial sepsis

Abstract: A severely ill 2-month-old female infant was admitted with meningitis and septicaemia caused by Streptococcus pneumoniae. The patient, who also had an acute cytomegalovirus (CMV) infection, revealed the typical clinical and biochemical characteristics of type I tyrosinaemia (TIT). Clinical evidence of severe hepatocellular damage was shown, but urinary succinylacetone was not detected. The diagnosis of TIT was finally confirmed by decreased activity of fumarylacetoacetase (FAA) in skin fibroblasts from the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Positive blood cultures for bacteria and fungi were reported in 15% of the emergency room visits of infants with methylmalonic acidaemia, propionic acidaemia and branched‐chain aminoacidaemia (3). Few reports previously described sepsis, meningitis and cytomegalovirus infection as the presentation of hereditary tyrosinaemia type I (HT‐1) (4).…”
Section: Discussionmentioning
confidence: 99%
“…Positive blood cultures for bacteria and fungi were reported in 15% of the emergency room visits of infants with methylmalonic acidaemia, propionic acidaemia and branched‐chain aminoacidaemia (3). Few reports previously described sepsis, meningitis and cytomegalovirus infection as the presentation of hereditary tyrosinaemia type I (HT‐1) (4).…”
Section: Discussionmentioning
confidence: 99%
“… 1 These are several reports of invasive pneumococcal disease (IPD) with HT1. Wabitsch et al 2 reported a severely ill 2‐month‐old female infant with meningitis and septicaemia caused by SP and HT1. Gill and Lipscomb 3 reported a 3‐month‐old, previously healthy girl diagnosed with primary pneumococcal peritonitis associated with HT1.…”
Section: Figurementioning
confidence: 99%
“…3 Few other case reports have highlighted this rare entity. 4 5 Detection of tyrosinemia is common in the West due to newborn screening programs for metabolic diseases. Our patient had tyrosinemia and CMV infection with very high viral load.…”
mentioning
confidence: 99%